2013
DOI: 10.5152/jtgga.2013.53179
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin treatment results in regression of endometriotic lesions in an ooferectomized rat endometriosis model

Abstract: Objective: We aimed to determine the effects of melatonin treatment on endometrial implants in an oopherectomized rat endometriosis model. Material and Methods:This study is a prospective, randomised, controlled experimental study. It was carried out at the Experimental Research Center of Yeditepe University (YUDETAM). Twenty-two, female, non-pregnant, nulligravid Spraque-Dawley albino rats were included in our study. Endometriosis was surgically induced in oopherectomized rats. Rats were randomised into two g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Melatonin is effective in treating experimental endometriosis induced by implanting human endometriotic cells in SCID mice [ 14 ]. Kocadal et al [ 13 ] reported that melatonin caused a regression of endometriotic lesions and an improvement in their histopathological scores in an oophorectomized rat endometriosis model.…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin is effective in treating experimental endometriosis induced by implanting human endometriotic cells in SCID mice [ 14 ]. Kocadal et al [ 13 ] reported that melatonin caused a regression of endometriotic lesions and an improvement in their histopathological scores in an oophorectomized rat endometriosis model.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Ke et al (2021) investigated the activity of MMP-3 and its relationship with MMP-9 during the onset of endometriosis in an experimental mouse model, and showed that MMP-3 plays a role in the early phases of endometriosis, while MMP-9 plays a role in the later phase. Melatonin, therefore, should be considered a potential therapeutic agent for the treatment of endometriosis [57].…”
Section: Fig 1 Effect Of Melatonin On Gynecologic Disordersmentioning
confidence: 99%
“…Following sterilization of the abdominal wall with 10% povidone-iodine, heating pads were applied until the animal regained consciousness. To induce the formation of endometriotic implants in autologous tissues, 50 μg/kg of estrogen was administered subcutaneously to the rats twice weekly [16].…”
Section: Surgical Procedures (Step 1: Implantation Of Endometriotic T...mentioning
confidence: 99%